Paraguay : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report, 2020)
This paper presents Paraguay's Request for Purchase Under the Rapid Financing Instrument (RFI). In March 2020, Paraguay was hit by the Covid-19 epidemic, which has created fiscal and balance of payments needs. The authorities' policy response to the epidemic has been timely, but limited access to financing and a weakened fiscal position constrain the ability to pursue a deeper emergency response. The Paraguayan authorities are requesting financial assistance under the IMF's RFI to address the urgent balance of payments needs associated with the Covid-19 epidemic. Given the urgency of their request, there is no time to put in place a full-fledged upper credit tranche program, and the authorities are of the view that they can make suitable adjustments to manage their medium-term balance of payments challenges. In order to prevent the emergence of permanently high deficits after the crisis, Paraguay should return to the deficit ceiling under the Fiscal Responsibility Law. The exchange rate should continue to function as shock absorber, and monetary policy should focus on inflation targeting.